2011
DOI: 10.1007/s00542-011-1356-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural, morphological and micromechanical studies on fly ash reinforced PMMA composites

Abstract: This paper is focused on the study of the structural, morphological, mechanical and microhardness studies on Fly ash reinforced PMMA composites. Fly ash reinforced PMMA composites have been prepared with the sol-gel method. Fourier transformed infrared (FT-IR) spectroscopy, X-ray diffraction, microhardness and atomic force microscopy (AFM) studies have been done on prepared composite. The AFM images confirm the presence of fly ash particles in nanophase within the PMMA matrix. The crystalline size of the in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It is observed that fly ash with smaller particles showed higher value of tensile strength. The percentage elongation at break also decreases [10] on addition on filler as shown in Fig. 2.…”
Section: Morphological Propertiesmentioning
confidence: 72%
See 1 more Smart Citation
“…It is observed that fly ash with smaller particles showed higher value of tensile strength. The percentage elongation at break also decreases [10] on addition on filler as shown in Fig. 2.…”
Section: Morphological Propertiesmentioning
confidence: 72%
“…[6,7] In this investigation we studied the effect of fly ash with three varying particle sizes and concentration on the properties of PTT. Recently many investigators studied the effect of fly ash on the properties of thermoplastics and thermosets [8][9][10][11][12][13][14][15]. Fly ash is the finely divided mineral residue resulting from the burning of pulverised coal in thermal power stations.…”
Section: Introductionmentioning
confidence: 99%
“…It is clearly evident from Fig. 7c that PMMA film has smooth surface which indicates the presence of planarized macromolecular chains [20]. Incorporation of MACNF into PMMA matrix helped in the development of triangular pattern, that is, within PMMA matrix (Fig.…”
Section: Resultsmentioning
confidence: 95%